Arabic Language and Cultural Identity: A Systematic Review of Sociolinguistic Literature - Aditya, Viqri; Rafli, Zaenal; Amrulloh, Muhammad Afif; Erlina , Erlina (Ta'limi | Journal of Arabic Education and Arabic Studies, 2025)
The Arabic language plays a significant role in shaping and expressing the cultural identity of Muslim communities, both in the Arab world and within diaspora communities. This study aims to present a systematic review of academic literature examining the relationship between Arabic language and cultural identity from a sociolinguistic perspective. Using a qualitative literature study approach, data were obtained from twenty selected scholarly sources and analyzed using thematic analysis techniques. The findings indicate that Arabic serves not only as a communication tool but also as a religious, ethnic, and national symbol that mediates identity construction through practices such as diglossia, code-switching, and code-mixing. Dialectal variations and the use of Arabic in digital media further strengthen cosmopolitan and religious identities. This study also highlights the influence of globalization, migration, and technological transformation on the position of Arabic in the contemporary social landscape. By integrating theories of linguistic identity, language ideology, and linguistic anthropology, this research produces a new conceptual synthesis that explains the multidimensional relationship between Arabic language and cultural identity. These findings are expected to serve as theoretical and methodological foundations for future studies in linguistics, education, and Islamic cultural studies.